Effect of simulated gastrointestinal digestion and fermentation on polyphenolic content and bioactivity of brown seaweed phlorotannin‐rich extracts. Issue 11 (29th August 2017) - Corona, Giulia; Coman, Maria Magdalena; Guo, Yuxuan; Hotchkiss, Sarah; Gill, Chris; Yaqoob, Parveen; Spencer, Jeremy P. E.; Rowland, Ian
Abstract : Scope: Unlike other classes of polyphenols, there is a lack of knowledge regarding brown seaweed phlorotannins and their bioactivity. We investigated the impact of in vitro gastrointestinal digestion and colonic fermentation on the bioactivity of a seaweed phlorotannin extract from Ascophyllum nodosum and its high molecular weight (HMW) and low molecular weight (LMW) fractions. Methods and Results: The highest phlorotannin and total polyphenol (TP) concentration was observed in the HMW fraction. Antioxidant capacity broadly followed phlorotannin and TP levels, with HMW having the highest activity. Both gastrointestinal digestion (GID) and colonic fermentation (CF) significantly affected phlorotannin and TP levels, and antioxidant capacity of the extract and fractions. Despite this, in HT‐29 cells, all GID extracts significantly inhibit cell growth, whereas CF extracts effectively counteracted H2 O2 induced DNA damage. Conclusion: Although phlorotannins, TP levels and antioxidant power of the extracts were strongly reduced after in vitro digestion and fermentation, their anti‐genotoxic activity and cell growth inhibitory effect in colon HT‐29 cells was maintained and enhanced. HMW was the most effective fraction, indicating that the high molecular weight phlorotannins potentially exert a stronger beneficial effect in the colon. Abstract : The impact of in vitro gastrointestinal digestion and colonic fermentation on the stability and bioactivity of a seaweed phlorotannins is examined. An ethanolic extract from Ascophyllum nodosum rich in phlorotannins, and its high molecular weight (HMW) and low molecular weight (LMW) fractions were utilized. Both gastrointestinal digestion (GID) and colonic fermentation (CF) significantly affected polymeric phlorotannins, total polyphenol levels, and antioxidant activity of the extract and fractions. Despite this, the anti‐genotoxic activity and cell growth inhibitory effect of the extracts in colon HT‐29 cells was maintained and enhanced. HMW was the most effective fraction, indicating that the high molecular weight phlorotannins potentially exert a stronger beneficial effect in the colon.